Teaching English Vocabulary Using Comic Media - Muhammad Hasbi; Muh. Miftahul Khaer; Fitriyani Bakri; Abdul Halim; Adi Isma (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
English has become an elective subject in Elementary Schools (SD) but not all schools are able to organize it since they do not have English teachers. Responding to this, this community service activity was carried out with the aim of introducing English vocabularies to students of SD Inpres Bertingkat Tabaringan I, Makassar City using interesting teaching media in the form of comics. This activity was carried out in the form of additional courses outside of school hours which were held for 10 meetings and followed by students in grades III and IV. The media used in teaching English vocabulary was in the form of power points using comic characters that children like. During the activity, students looked enthusiastic and very excited to participate in this activity because there were comic characters presented together with the English vocabulary being taught. This proves that the main purpose of using comic media in teaching English vocabulary was successful and the majority of course participants were also able to pronounce and memorize new vocabularies given by the instructor